2018
DOI: 10.1177/1071100717746627
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Juvenile Allogenous Articular Cartilage and Bone Marrow Aspirate Concentrate Versus Microfracture With and Without Bone Marrow Aspirate Concentrate in Arthroscopic Treatment of Talar Osteochondral Lesions

Abstract: Level III, comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 75 publications
1
44
0
Order By: Relevance
“… a RTS, return to sports. b References 6, 15, 17, 18, 20, 26, 29, 35, 38, 41, 43, 47, 54, 58 60, 69, 75, 76, 85, 88, 92, 94. c Range of means of original data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a RTS, return to sports. b References 6, 15, 17, 18, 20, 26, 29, 35, 38, 41, 43, 47, 54, 58 60, 69, 75, 76, 85, 88, 92, 94. c Range of means of original data.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of outcome measures were reported within this group. The FAOS sports score was reported by 2 studies, 35,54 1 study reported on the Foot and Ankle Disability Index (FADI) sports subscale, 8 and 1 study reported on the German Foot Function Index (FFI-D) sports subscale. 25 Because of low reporting, these scores were not further analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study comparing DeNovo NT and microfracture in talar osteochondral defects found no differences in patient-reported outcomes or repair tissue quality. 67…”
Section: Methodsmentioning
confidence: 99%
“…However, no differences were observed between placebo and treated knee 6 months after treatment [60] and 12 months after treatment [61]. Two studies were designed to treat osteochondral lesions of the talus, both used juvenile allogenic chondrocyte implantation (JACI) and BMAC [62,63]. The first study compared the pre- to postoperatively outcomes [62].…”
Section: Bone Marrow Aspirate Concentrate (Bmac)mentioning
confidence: 99%
“…Unfortunately, this study did not quantify the cells and did not mention the system used to prepare the BMAC. In the second study, the authors used the Magellan system to produce the BMAC, however they did not quantify the number of progenitor cells [63]. The authors compared the microfracture (MF) with JACI–BMAC.…”
Section: Bone Marrow Aspirate Concentrate (Bmac)mentioning
confidence: 99%